Effect of the inclusión of herbal phosphatidylcholine on palatability, digestibility and metabolisable energy of the diet in dogs - Mendoza Martínez, Germán D.; López, Miguel A.; Hernández García, Pedro A.; Ríos Hilario, Josué J.; González, Javier; Trujillo, Adrian Gloria (Austral Journal of Veterinary Sciences, 2021)
This study aimed to evalúate the palatability, nutrient digestibility, metabolisable energy (ME) and faecal characteristics of diets in dogs fed increasing levels of herbal phosphatidylcholine (herbal mix) versus an unsupplemented diet (with only 377 mg choline provided by 1 kg food) or choline chloride (2000 mg choline/kg food) in 40 adult dogs. In experiment 1, a palatability test was conducted to make two pairwise comparisons: 0 versus 200; and 0 versus 400 mg/kg herbal mix. In experiment 2, a digestibility test was performed to evaluate herbal mix at 0, 200, 400 and 800 mg/kg and 2000 mg choline provided by choline chloride. Results from experiment 1 indicated that the dogs preferred diets containing herbal mix to the unsupplemented diet (P<0.05). In experiment 2, nutrient digestibility and faecal characteristics were not influenced by the treatment (P<0.059). The inclusion of 400 mg/kg of herbal mix increased the ME (quadratic effect, P<0.01). In conclusion, the results of this study indicate that the inclusion of a herbal mix rich in phosphatidylcholine (1.6%) and other methylated metabolites at 400 mg/kg can fully replace choline chloride in dog diets.